2018
DOI: 10.2196/10471
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Engagement and Weight Loss Through Personal Coaching and Cell Phone Interventions in Young Adults: Randomized Controlled Trial

Abstract: BackgroundUnderstanding how engagement in mobile health (mHealth) weight loss interventions relates to weight change may help develop effective intervention strategies.ObjectiveThis study aims to examine the (1) patterns of participant engagement overall and with key intervention components within each intervention arm in the Cell Phone Intervention For You (CITY) trial; (2) associations of engagement with weight change; and (3) participant characteristics related to engagement.MethodsThe CITY trial tested two… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 38 publications
1
65
0
Order By: Relevance
“…A cohort study showed that more app-based recordings were associated with greater weight loss [ 31 ]. In the Cell Phone Intervention For You (CITY) trial, increasing app use per day was associated with increasing weight loss [ 34 ]. In our study, we observed a tendency for greater weight loss as the number of recordings increased, albeit without statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study showed that more app-based recordings were associated with greater weight loss [ 31 ]. In the Cell Phone Intervention For You (CITY) trial, increasing app use per day was associated with increasing weight loss [ 34 ]. In our study, we observed a tendency for greater weight loss as the number of recordings increased, albeit without statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The “cell phone” (CP) group was provided with a smartphone app which included a variety of behavioral change techniques, e.g., self-monitoring (diet, physical activity, and weight) and in-app prompting. The “personal coaching” (PC) group attended group sessions and received phone calls from coaches in addition to app-assisted self-tracking of weight, diet, and physical activity, but no in-app prompting [51,67]. Results revealed that CP participants had no weight loss advantages compared to controls at any time point (6, 12, and 24 months), while weight loss after 6 months was significantly higher (1.92 kg; CI 3.17, 0.67; p = 0.003) in the PC group than in the control group.…”
Section: Smartphone Applications (Apps) and Wearable Devices (Actimentioning
confidence: 99%
“…Differences in mean weight loss at 24 months were not significant between intervention groups [51]. Besides that, a further publication about the CITY study from 2018 revealed that there was an association between engagement and weight loss during the first 6 intervention months [67]. Compared to PC participants, engagement and self-monitoring of weight were higher in CP participants.…”
Section: Smartphone Applications (Apps) and Wearable Devices (Actimentioning
confidence: 99%
See 2 more Smart Citations